KNOWLEDGE AND ATTITUDES ABOUT THE VSC IN WOMEN OF CHILDBEARING AGE IN THE TOWN OF NUEVA CAJAMARCA REGION OF SAN MARTIN - Paredes, Luis (2015)
OBJECTIVE: To determine knowledge and attitudes about Voluntary Surgical Contraception (VSC) and means of information through which they inquire on this subject, in the locality of New Cajamarca, province of Rioja. DESIGN: Prospective, descriptive study. RESULTS: A population sample was taken from women in fertile age, in those who a questionnaire was used to I gather information. 98,5% answered that they did not know what is VSC and 85% did not know the risks, 53,5% responded that VSC imposed, 34,5% that they wish VSC to be usuary of AQV and the 40,5% responded that they would not like that other people found out to be usuary this method. They mentioned the health personnel as the main informers of VSC and I% mentioned the Church. The people refer that radio and television should give information. CONCLUSION: In the population studied knowledge of the VSC is minimum and the attitude towards this method was positive. They consider the role of the establishment of health in the information of this subject.